Ni(OH)2 Decorated Pt-Cu Octahedra for Ethanol Electrooxidation Reaction - Hong, Youngmin; Kim, Hee Jin; Lee, Hye Jin; Kim, Jeonghyeon; Choi, Sang-Il (Frontiers in Chemistry, 2019)
Here we report the synthesis of 9 nm Ni(OH)2 decorated Pt-Cu octahedra (Ni(OH)2-PtCu) in one-pot synthesis for ethanol oxidation reaction (EOR) electrocatalysis in acidic electrolyte. To prepare Ni(OH)2-PtCu octahedra, CO gas was directly introduced in a reaction process as selective capping agents on the PtCu(111) facet. Ni(OH)2 was naturally deposited on the Pt-Cu octahedra during the synthesis. Carbon supported Ni(OH)2-PtCu (Ni(OH)2-PtCu/C) as an EOR catalyst showed enhanced CO tolerance due to the existence of oxophilic Ni(OH)2 on the surface of Pt-Cu, facilitating water dissolution to produce OH adsorption and to promote complete CO oxidation to CO2. In addition, Pt-Cu alloy composition also showed improvement of CO tolerance because of modified d-band structure of the Pt atoms, thereby weakening the binding strength of CO on the catalysts. Therefore, the Ni(OH)2-PtCu/C showed enhanced EOR activity and durability compared to the Pt-Cu octahedra and commercial Pt/C counterparts.